Eliminating rare earth permanent magnets on low‐speed high‐torque machines: A performance and cost comparison of synchronous reluctance machines, ferrite permanent magnet‐synchronous reluctance machines and permanent magnet synchronous machines for a direct‐drive elevator system. Issue 3 (9th February 2021) - Artetxe, Gurutz; Caballero, Damian; Prieto, Borja; Martinez‐Iturralde, Miguel; Elosegui, Ibon
Abstract: In the last few years, the reduction of the dependency on rare‐earth magnets has been one of the main concerns for electrical machine manufacturers. Synchronous reluctance machines (SynRMs) and ferrite permanent magnet‐assisted synchronous reluctance machines (PMa‐SynRMs) are emerging as alternatives to permanent magnet synchronous machines (PMSMs) in several applications. In low‐speed high‐torque applications, PMSMs with large amounts of rare‐earth magnets are commonly employed. Thus, it is of particular interest to replace PMSMs by SynRMs or PMa‐SynRMs. This article studies the feasibility of using SynRMs and ferrite PMa‐SynRMs for a direct‐drive elevator system. The challenge lies in obtaining performance characteristics comparable to those of PMSMs, but without resorting to the use of rare‐earth permanent magnets. The main criteria for designing SynRMs and PMa‐SynRMs for low‐speed high‐torque applications are presented. Afterwards, a SynRM and a ferrite PMa‐SynRM are designed for 160 rpm 200 Nm rated conditions, and a performance and cost comparison between these machines and a commercial PMSM is conducted.